SAR Signal Reconstruction from Non-Uniform Displaced Phase Centre Sampling - Krieger, Gerhard; Gebert, Nicolas; Moreira, Alberto (IEEE Geoscience and Remote Sensing Symposium (IGARSS), 2004)
The displaced phase centre (DPC) technique will enable a wide swath SAR with high azimuth resolution. In a classic DPC system, the PRF has to be chosen such that the SAR carrier moves just one half of its antenna length between subsequent radar pulses. Any deviation from this PRF will result in a non-uniform sampling of the synthetic aperture. This paper shows that an unambiguous reconstruction of the SAR signal is also possible in case of such a non-optimum PRF. For this, an innovative reconstruction algorithm is derived, which enables a recovery of the unambiguous Doppler spectrum also in case of a non-uniform sampling of the synthetic aperture. This algorithm will also have a great potential for multistage satellite constellations as well as the dual receive antennas in Radarsat II and TerraSAR-X.
DLR Import::2019-04-03